2016
DOI: 10.1016/j.matdes.2016.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Solid–liquid interface dynamics during solidification of Al 7075–Al2O3np based metal matrix composites

Abstract: Interactions between the solidification front and the remaining suspended particles take place during solidification of particles reinforced composites. The particles are either engulfed by the solidification front or pushed by the solid-liquid interface. In this study, the relation of distribution and clustering degree of nano-Al 2 O 3 in Al7075 with the microstructure of alloy was investigated by conducting casting experiment. A hydrodynamic model for calculating the critical interface velocity required to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…Sajjadi et al [2] reported that for the A356 alloy with 1.0 wt.% Al 2 O 3np (50 nm), the compressive strength is 2.13 times larger than that obtained by adding the same amounts of micro-sized Al 2 O 3 particles (20 μm), suggesting that particle size greatly affects the mechanical properties of composites. In our previous study on particle pushing [33], we reported the agglomerates of Al 2 O 3np were easily pushed toward eutectic regions. The presence of agglomerates hindered the flow of liquid phases, thus causing the difficulties in feeding shrinkage porosity.…”
Section: Constitutive Relationship Of Nanocompositesmentioning
confidence: 94%
“…Sajjadi et al [2] reported that for the A356 alloy with 1.0 wt.% Al 2 O 3np (50 nm), the compressive strength is 2.13 times larger than that obtained by adding the same amounts of micro-sized Al 2 O 3 particles (20 μm), suggesting that particle size greatly affects the mechanical properties of composites. In our previous study on particle pushing [33], we reported the agglomerates of Al 2 O 3np were easily pushed toward eutectic regions. The presence of agglomerates hindered the flow of liquid phases, thus causing the difficulties in feeding shrinkage porosity.…”
Section: Constitutive Relationship Of Nanocompositesmentioning
confidence: 94%
“…91,97 The presence of Si in cast Al alloys can improve the dispersion of TiB 2 particles, 98 although the TiB 2 particles are still partially segregated in the eutectic regions because of the pushing mechanism during solidification. [99][100][101] The typical microstructure of Al/TiB 2 composites is shown in Figure 12. The Al-9Si-1Mg-0.7Cu/TiB 2 composite can be produced with clean, smooth, and well-bonded interfaces between the aluminum matrix and TiB 2 particles between 25 and 3,000 nm.…”
Section: Al/tib 2 Compositesmentioning
confidence: 99%
“…The inadequacy of metals and alloys in providing both strength and stiffness to a structure has led to the development of various composites particularly metal matrix composites (MMCs) [1,2].…”
Section: Introductionmentioning
confidence: 99%